ANKLE ARTHRODESIS AFTER COMBAT RELATED INJURIES - Piatkovskyi, Volodymyr; Turchin, Olena; Omelchenko, Taras; Yevlantieva, Tetiana; Kharchyk, Vasyl’; Liabakh, Andrii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Combat related injuries of the ankle joint (AJ) are often accompanied by severe changes in the musculoskeletal system, which require arthrodesis of the damaged joints in the final stage of treatment. Objective. To analyze the results of AJ arthrodesis in patients after combat related injuries, to highlight aspects of the use of different fixation methods. Methods. AJ arthrodesis was performed in 21 patients with the consequences of severe combat related injuries of the posterior part of the foot. An intramedullary locked rod (18 patients), screws (2 patients) and an Ilizarov-type external fixation device (EFD) were used for fixation in one patient. The results were assessed no earlier than 6 months after the start of loading using the AOFAS (posterior part), SMFA (short musculoskeletal functional assessment) and EQ-5D-5L (mobility, self-care, usual activity, pain, anxiety, VAS) scales and questionnaires. Results: In the specified terms, the results were traced in 21 patients. A differential approach was used in choosing the method of fixation of the AJ. A significant increase in function was obtained according to the AOFAS, SMFA and EQ-5D-5L scales (p ˂ 0.001). Conclusions. AJ arthrodesis in patients with the consequences of severe combat related injuries allows to restore the resistance of the limb and is the final stage of treatment of these patients.